CYP2C19 metabolizer phenotypes may affect the efficacy of statins on lowering small dense low-density lipoprotein cholesterol of patients with coronary artery disease - Dai, Ruozhu; Zhao, Xiaoyu; Zhuo, Huilin; Wang, Wei; Xu, Yue; Hu, Zixin; Zhang, Tiexu; Zhao, Jiangman (Frontiers in Cardiovascular Medicine, 2022)
Background: Dyslipidemia is a major cause of arteriosclerotic cardiovascular disease (ASCVD), and low-density lipoprotein-cholesterol (LDL-C) is the target to be reduced to prevent disease progression. Small dense low-density lipoprotein-cholesterol (sdLDL-C) has been proven to be a more effective biomarker than LDL-C for ASCVD primary and secondary prevention. CYP2C19 is an important drug metabolism gene. This study aims to investigate the relationship between sdLDL-C and coronary artery disease (CAD) risk factors, and explore CYP2C19 metabolizer phenotypes’ influence on the sdLDL-C lowering efficacy of statins. Methods: This study recruited 182 CAD patients and 200 non-CAD controls. Baseline laboratory indices of fasting blood were detected, including blood lipids, glucose, and creatinine. In addition, LDL-C subfractions were separated and quantified. Gene polymorphisms of SLCO1B1 and CYP2C19 were detected in CAD patients. The LDL-C subfraction levels of CAD patients were followed up after statin drug treatment. Results: Total cholesterol, LDL-C, LDLC-2 to 7, and sdLDL-C levels of CAD patients were significantly higher than those in non-CAD controls. Meanwhile, sdLDL-C (AUC=0.838) and LDLC-4 (AUC=0.835) showed the outstanding performance to distinguish CAD patients from controls. Based on CYP2C19 metabolizer phenotypes, 113 CAD patients were divided into extensive metabolizer (EM, n=49), intermediate metabolizer (IM, n=52), and poor metabolizer (PM, n=12) groups. The patients with IM and PM metabolizer phenotypes had better sdLDL-C lowering efficacy after taking statin drugs than patients with EM phenotype (P=0.0268, FDR=0.0536). The SLCO1B1 genotype had no significant impact on the efficacy of statins (P=0.1611, FDR=0.1611). Conclusions: SdLDL-C and LDLC-4 showed better performance for CAD risk screening than other blood lipids such as LDL-C. CYP2C19 metabolizer phenotypes had the potential to predict statins’ sdLDL-C lowering efficacy.